Regrow your veggies : growing vegetables from roots, cuttings and scraps - Raupach, Melissa; Lill, Felix (CompanionHouse Books, an imprint of Fox Chapel Publishers International Ltd., 2020)
"No need to keep buying the same vegetables you eat all the time over and over again. Regrow Your Veggies is an insightful guide that provides effective propagation techniques to recycle and regrow more than 20 popular vegetables right at home! Learn how to have a source of fresh and healthy vegetables close by, from onions and sweet potatoes to pineapples and mangoes, reduce waste, and know how to prevent and solve issues with pesky pests and pathogens. Get the most out of your favorite foods and produce your own produce!" -- Amazon.com.